Finding of more than one hydatid within a pulmonary adventitial cavity: pathogenic discussion on 15 observations - Delgado, Bolívar; Díaz, Barret; Macedo, Juan C (Cirugía del Uruguay, 1972)
The interesting problem of hydatic pathology is studied, which involves the discovery of more than one hydatid within a pulmonary adventitial cavity. The different pathogenic mechanisms are analyzed: local secondary seeding (the most frequent), exogenous cotical vesiculation, common nesting of 2 hexacanth embryos and adventitial "usury".